PENGARUH METODE PROYEK TERHADAP KEMAMPUAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI DUSUN PENENDEM KECAMATAN KERUAK - Astiti Sofyati Zahra; Baik Nilawati Astini; Ika Rachmayani (Indonesian Publication Center, 2020)
This study aimed to determine the effect of project method on children's social emotional skill at the age of 5 to 6 in Penendem village, Keruak sub-district. The type of research used quantitative comparative method. The research use experimental design which is in the form of pretest- posttest group design. In this research, the technique of the data collection were through provided treatment, observation by using research instrument, and documentation. The data collected were analyzed using statistic non-parametris method. The research subject in this study were the early childhood at the age of 5 to 6 in Penendem village, Keruak sub-district. Based on the research outcome, it shows that the social and emotional skill of the children at the age of 5 to 6 in Penedem village, Keruak sub-district before the the project method implemented, the pre-test score was at the average of 58,8% which mean that the social emotional skill of the children were still in lower level development. In contrast, atfter the project method was implemented, the post-test score was improve significantly to 71,3% at the average which mean that the social emotional skill of the children were in higher level developement. Thus it can be concluded that every child has a good potential social emotional skill to develop primely if they can be stimulated by using an appropriate and effective method.